Molecular genetics made simple - Kassem, HSh; Girolami, F.; Sanoudou, D. (Glob Cardiol Sci PractGlob Cardiol Sci PractGlob Cardiol Sci Pract, 2012)
Genetics have undoubtedly become an integral part of biomedical science and clinical practice, with important implications in deciphering disease pathogenesis and progression, identifying diagnostic and prognostic markers, as well as designing better targeted treatments. The exponential growth of our understanding of different genetic concepts is paralleled by a growing list of genetic terminology that can easily intimidate the unfamiliar reader. Rendering genetics incomprehensible to the clinician however, defeats the very essence of genetic research: its utilization for combating disease and improving quality of life. Herein we attempt to correct this notion by presenting the basic genetic concepts along with their usefulness in the cardiology clinic. Bringing genetics closer to the clinician will enable its harmonious incorporation into clinical care, thus not only restoring our perception of its simple and elegant nature, but importantly ensuring the maximal benefit for our patients.
Kassem, Heba ShGirolami, FrancescaSanoudou, DespinaengReviewQatar2012/01/01 00:00Glob Cardiol Sci Pract. 2012 Jul 4;2012(1):6. doi: 10.5339/gcsp.2012.6. eCollection 2012.